THE INFLUENCE OF LEADERSHIP AND ORGANIZATIONAL CLIMATE ON THE PERFORMANCE OF MUNUNGREJO VILLAGE APPARATUS - Riyadi, Octhavian Hafis Adinaro; Ambarwat, Arie; Raharja, Wildan Taufik (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2024)
This study aims to determine and analyze the simultaneous and partial influence of leadership variables, and organizational climate on the performance of Munungrejo village employees, Ngimbang District, Lamongan Regency. The analytical tool used is a questionnaire distributed to 38 village officials which produces an R value of 0.576, indicating the relationship between the independent variable and the dependent variable is strong, and the R2 value is 0.331 or 33.1%. So that the variables of leadership, and organizational climate can explain employee performance and the remaining 66.9% is explained by other variables. The results of the F test of independent variables have a significant effect on the performance variable (Y), the value of Fcount is 4.959 > Ftable 2.87, at a significance of 0.018 < sig. (α) of 0.05. The results of the t test, the leadership variable (X1) has no significant effect on performance (Y), with a tcount of -1.774 < ttable 2.03011, and a significance value of 0.091 > 0.05. Then the organizational climate variable (X2) has a significant effect on performance (Y) with a significance value of 0.012 <0.05 and a tcount value of 2.773 > ttable 2.03011